2014
DOI: 10.1111/dar.12226
|View full text |Cite
|
Sign up to set email alerts
|

Denial of prescription analgesia among people who inject drugs in a Canadian setting

Abstract: Introduction and Aims Despite the high prevalence of pain among people who inject drugs (PWID), clinicians may be reluctant to prescribe opioid-based analgesia to those with a history of drug use or addiction. We sought to examine the prevalence and correlates of PWID reporting being denied prescription analgesia (PA). We also explored reported reasons for and actions taken after being denied PA. Design and Methods Using data from two prospective cohort studies of PWID in Vancouver, Canada, multivariate logi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
48
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 41 publications
2
48
0
Order By: Relevance
“…Also, with limited time or training, it is difficult for clinicians to distinguish opioid tolerance and opioid-induced hyperalgesia in this population, though the two are important to distinguish given that their treatment is diametrically different 34 . For these reasons, clinicians may tend to under-prescribe analgesics to persons with substance use disorders or to prescribe analgesics less prone to abuse though less effective 38 .…”
Section: Discussionmentioning
confidence: 99%
“…Also, with limited time or training, it is difficult for clinicians to distinguish opioid tolerance and opioid-induced hyperalgesia in this population, though the two are important to distinguish given that their treatment is diametrically different 34 . For these reasons, clinicians may tend to under-prescribe analgesics to persons with substance use disorders or to prescribe analgesics less prone to abuse though less effective 38 .…”
Section: Discussionmentioning
confidence: 99%
“…While the rate of prescribing in the USA dropped from a high of 81.3 per 100 persons in 2012 to 58.5 per 100 persons in 2017,3 the death rate attributable to opioids continues to rise, and prescription opioid misuse has remained fairly stable since 2010 3. While this result may seem unexpected, it is not entirely surprising given observed transitions from prescription opioid to heroin use in the USA, as well as evidence from Canada indicating that many individuals acquire heroin or diverted opioids from drug markets when denied opioids from physicians 4. These dynamics are consistent with evidence from a range of settings indicating that when access to one substance is restricted, most individuals will transition to using an alternative, which in many cases will be more dangerous than standardised doses of prescription opioids.…”
mentioning
confidence: 87%
“…A recent study showed that despite the high prevalence of pain among people who inject drugs, clinicians may be reluctant to prescribe opioid-based analgesics to those with a history of drug use or addiction, especially in people already enrolled in MMT [17]. …”
Section: Introductionmentioning
confidence: 99%